Impact of COVID-19 pandemic on the incidence and severity of myasthenia gravis in Korea: using National Health Insurance Service database - Kim, Sooyoung; Lee, Eun Kyoung; Kim, Hasung; Kim, Hoseob; Sohn, Eunhee (Frontiers in Neurology, 2024)
Background This study investigated the impact of COVID-19 pandemic on the incidence and severity of myasthenia gravis (MG) using the National Health Insurance Service (NHIS) database in Korea. Methods We analyzed data from patients with MG in the NHIS registry from 2015 to 2021. MG was defined as (1) patients aged ≥18 years with the G70.0 code, and (2) patients who visited tertiary hospitals regarldless of department in Korea (outpatient clinics at least twice or hospitalization at least once), and (3) patients who were prescribed pyridostigmine as MG medications at least once. We designated pre-COVID-19 as 2019 and post-COVID-19 as 2021 and analyzed the MG incidence and prevalence in 2019 and 2021. We compared the clinical data of patients with MG between the two years. MG exacerbation was defined as the administration of intravenous immunoglobulin or plasma exchange. Analysis of COVID-19 cases was conducted using an integrated database from the Korea Disease Control and Prevention Agency and NHIS. Patients with MG were divided into two groups according to COVID-19 status to compare their clinical characteristics. Results A total of 6,888 and 7,439 MG cases were identified in 2019 and 2021, respectively. The standardized incidence was 1.56/100,000 in 2019, decreasing to 1.21/100,000 in 2021. Although the frequency of MG exacerbations was higher in 2019, there were no differences in the number and duration of hospitalizations, duration of ICU stays, hostalization expense, and mortality between 2019 and 2021. Patients with MG and COVID-19 had a higher frequency of MG exacerbations than patients without COVID-19, but there were no differences in the number and duration of hospitalizations, hospitalization expense, and mortality. Conclusion This study was the first nationwide population-based epidemiological study of MG during COVID-19 pandemic in Korea. The incidence of MG decreased during COVID-19 pandemic, and the severity of MG was not affected by COVID-19.